Adequate Intake of Docosahexaenoic Acid for Adults: NHANES 2015–2016 (P18-032-19). (13th June 2019) - Brault, Hayven; Miketinas, Derek
Abstract: Objectives: The Dietary Guidelines for Americans 2015–2020 recommend adults consume 250 mg of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)daily, or the equivalent of 8 ounces of seafood/week. The objective of this study was to assess the prevalence of adequate intake of docosahexaenoic acid using data from the National Health and Nutrition Examination Survey (NHANES) 2015–2016. Methods: Data were obtained from the 2015–2016 version of the NHANES. Mean intake of DHA was estimated using the National Cancer Institute (NCI) method. Covariates included: sex, age, ethnicity, energy intake, and total fat intake. Cut-off values for adequate intake included: 125 mg, 200 mg, and 300 mg. Results: Mean DHA intake for the total sample of adults ( n  = 5854) was 6.68 mg. Of the total sample, 12.3%, 4.0%, and 1.2% met the 125 mg, 200 mg, and 300 mg cut-off values for adequate intake of DHA, respectively. Conclusions: These results indicate a high prevalence of suboptimal intake of DHA for adults. Only 12.3% adults meet half the recommended intake (125 mg) for EPA and DHA combined through DHA consumption. Less than 1.2% consumed enough DHA (300 mg) to satisfy the overall needs for both EPA and DHA. Funding Sources: No funding sources to declare.